Passed the Age of Puberty: Organizational Networks as a Way to Get Things Done in the Health Field; Comment on "Evaluating Global Health Partnerships: A Case Study of a Gavi HPV Vaccine Application Process in Uganda" - Patrick Kenis (Kerman University of Medical Sciences, 2017)
In this commentary I will demonstrate that the case study of Uganda's Human papilloma virus (HPV) vaccine application partnership provides an excellent example of widening our lens by evaluating the successful HP vaccine coverage from a network-centric perspective. That implies that the organizational network is seen as the locus of production and that network theories become indispensable to analyze the situation at hand. The case study is, as said, an excellent example of how this can be done and my comments have to be read as an endorsement and a broadening of the discussion of what Carol Kamya and colleagues have presented. It is demonstrated that an organizational network approach can be considered a serious and mature way in understanding public health issues.